2014
DOI: 10.1007/s10266-014-0189-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 30 % hydrogen peroxide on mineral chemical composition and surface morphology of bovine enamel

Abstract: A combination of atomic absorption spectroscopy (AAS), Fourier transform infrared spectroscopy (FTIR), scanning electronic microscopy (SEM), and gas adsorption techniques was used to characterize the effect of 30 % hydrogen peroxide (HP) on enamel surface. To perform the analyses of AAS, 1 ml of 30 % HP was added to 30 mg of a bovine enamel powder sample (150-200 µm fractions) for times of 5, 20, 60, 90, and 120 min; then 5 ml of the solution was withdrawn after each time period to measure [Ca(2+)] ions. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…In the present study, the results of microhardness test and SEM analysis, as expected, revealed that HP alone could result in significant microhardness loss and morphological change of enamel. These findings are consistent with studies (3,(8)(9)(10) that suggested that morphological change of enamel is due to the demineralization caused by acidic HP, while microhardness loss is due to the combined effects of demineralization and destruction of organic matter by HP. hydrogen peroxide induced enamel mineral loss after bleaching and this process can lead to demineralization of the enamel surface and compromise its mechanical properties.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, the results of microhardness test and SEM analysis, as expected, revealed that HP alone could result in significant microhardness loss and morphological change of enamel. These findings are consistent with studies (3,(8)(9)(10) that suggested that morphological change of enamel is due to the demineralization caused by acidic HP, while microhardness loss is due to the combined effects of demineralization and destruction of organic matter by HP. hydrogen peroxide induced enamel mineral loss after bleaching and this process can lead to demineralization of the enamel surface and compromise its mechanical properties.…”
Section: Discussionsupporting
confidence: 92%
“…(4,5) It is known that the oxidationreduction reaction of the bleaching agent might cause dissolution of the organic and inorganic dental matrix until only carbon dioxide and water remain. Additionally, it has been shown that bleaching with 35-38% hydrogen peroxides may change enamel morphology and alter mineral content (3,4,(8)(9)(10) . Thus, efforts have been made to achieve a protocol capable of remineralizing bleached enamel, recovering microhardness loss and surface alterations (11)(12)(13)(14)(15) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several side effects caused by whitening vital teeth have been reported in the literature, and the one that is most often cited is dental sensitivity [ 6 , 11 , 18 20 ], but there are others, such as a change in mechanical properties of enamel, dentin, and direct restorative materials [ 6 , 8 , 9 , 21 23 ], an increase in roughness of these tissues [ 1 , 8 , 13 , 24 30 ], and change in mineral content [ 1 , 12 , 20 , 25 , 29 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A literature review in 2007 [ 6 ] showed that, as of the date of publication, the studies were almost unanimous in stating that there was no change in mineral content in the enamel surface. However, many studies performed after that date have shown the opposite [ 1 , 13 , 21 , 26 , 30 33 ]. This is due to the wide variety of methodologies, without there being a well-defined protocol for this type of study, and the use of nonideal tests to measure loss of calcium and phosphorous in tooth enamel.…”
Section: Discussionmentioning
confidence: 99%